Systematic Literature Review: The Evolution of Adaptive Governance and Practice in the Context of the Environmental Crisis - Herizal Herizal; Saddam Rassanjani; Afrijal Afrijal; Muhkrijal Muhkrijal; Marno Wance (School of Postgraduate Studies, Diponegoro Univer, 2024)
This paper aims to clarify the understanding of the conceptual evolution of the adaptive governance framework, followed by an examination of implementation actions in the environmental setting. Since three approaches are recognized to be essential in navigating complex socio-ecological systems, namely adaptive management, adaptive co-management, and adaptive governance. This might lead to confusion and misunderstandings in adaptive concepts and practice. In this study, a systematic literature review was conducted using the Scopus database. A literature search was conducted in Mei 2023 using the keyword